2012
DOI: 10.2147/ijn.s34105
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and endocytosis of ICAM-1-targeting antibodies versus nanocarriers in the gastrointestinal tract in mice

Abstract: Drug delivery to the gastrointestinal (GI) tract is key for improving treatment of GI maladies, developing oral vaccines, and facilitating drug transport into circulation. However, delivery of formulations to the GI tract is hindered by pH changes, degradative enzymes, mucus, and peristalsis, leading to poor GI retention. Targeting may prolong residence of therapeutics in the GI tract and enhance their interaction with this tissue, improving such aspects. We evaluated nanocarrier (NC) and ligand-mediated targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Notably, all myeloid cells including DCs express β2 integrin (CD18). CD18 forms heterodimers with CD11a, CD11b, and CD11c (69) and contributes to cell-cell contact formation by binding to intracellular adhesion molecules (ICAMs), which may be expressed on gastric and intestinal epithelial cells (70, 71). Notably, adhesion of DCs to epithelial cells via β2 integrins would be consistent with our experimental observations that showed increased binding in the presence of Mn 2+ and decreased binding in the presence of EGTA.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all myeloid cells including DCs express β2 integrin (CD18). CD18 forms heterodimers with CD11a, CD11b, and CD11c (69) and contributes to cell-cell contact formation by binding to intracellular adhesion molecules (ICAMs), which may be expressed on gastric and intestinal epithelial cells (70, 71). Notably, adhesion of DCs to epithelial cells via β2 integrins would be consistent with our experimental observations that showed increased binding in the presence of Mn 2+ and decreased binding in the presence of EGTA.…”
Section: Discussionmentioning
confidence: 99%
“…Mane and Muro have investigated about this method and explained their experiment using anti-ICAM-antibodies which were surrounded over the nanoparticles. 52 On the oral administration of this antibody coated nanoparticle, it was found that after the exposure to enzymes present in GI tract, these antibodies were destructed while the nanoparticles got lodged in the duodenum. These scientists used techniques like transmission electron microscopy and energy dispersive X-ray in their experiments.…”
Section: Antibody Targeted Smart Polymer Systemmentioning
confidence: 98%
“…Evaluation of benefit to risk ratio is very essential as ADRs may weaken the life quality related to health and may therefore prevent successful treatment of the disorder. To improvise therapeutic efficiency, and to reduce the adverse drug reactions, selective drug accumulation inside the colon at the inflamed sites can be done with the help of nanocarriers based delivery systems supplemented and coupled with active targeting approaches like ligands (Mane and Muro, 2012). An expanding number of ligands for targeted drug delivery are studied for drug approaches related to drug targeting specific for colon.…”
Section: Critical Aspects Of Drug Delivery and Dosage Form Developmentsmentioning
confidence: 99%
“…Moreover, it is discerned to reduce the adverse reactions, by further improving the selective drug accumulation at inflamed sites within the colon. While according to Mane and Muro (2012) the biodistribution and cellular uptake of polystyrene nanoparticles coated with anti-ICAM-1 antibodies was evaluated. According to Nayak et al (2018), the current status of drug delivery technologies was explored and highlighted.…”
Section: Need Of Ligand Based Colon Targeted Drug Deliverymentioning
confidence: 99%